WM1-5 Predictors of retreatment of anterior communicating artery aneurysms after endovascular embolisation. Issue 3 (14th February 2019) - Borg, A; Grover, P; Schmitt, A
Abstract : Objectives: To establish recurrence and retreatment rates of anterior communicating artery aneurysms (ACom) after endovascular embolization and the complication rate of retreatment. To establish predicting morphological characteristics that would favour surgery or endovascular coiling. Design: Retrospective review of all ACom aneurysms treated at a single neurological centre over a thirteen-year period. Subjects: Patients undergoing endovascular treatment of ACom aneurysms. Methods: Aneurysm and patient characteristics were recorded for retreated patients. Analysis of retreatment predictors on imaging was made. Results: Between 2005 and 2018, 510 Acom aneurysms were treated, of which 456 presented with SAH and 54 were elective. Out of these, 36 underwent re-treatment. Out of the re-treated aneurysms 33 were identified from radiological follow up and three presented with a re-bleed. The complication rate from the second endovascular procedure was 5.6%. Four patients underwent surgical clipping after failed coiling. Retreatment was more likely in ruptured aneurysms. The dome shape, size (mm) and orientation, were recorded for both aneurysms requiring retreatment and aneurysms successfully excluded after the first procedure. Other parameters reported included time interval, coiling technique (balloon-assisted/stent-assisted). Conclusions: Recurrence of Acom aneurysms after coiling carries significant morbidity. Recognising predictors of recurrence would help identify those aneurysms that are better treated with surgery.